Social Pedagogy and Liberal Egalitarian Compensatory Programs: The Case of Head Start - Counsell, Shelly Lynn; Boody, Robert (Education Policy Analysis Archives, 2013)
Using Head Start as an example of a compensatory social program based on a liberal egalitarian view of justice, this paper shows how all such programs are fundamentally flawed. In spite of any good intentions, by creating a discourse of deficiency and attempting amelioration through segregation this approach contains the seeds of its own failure. And, indeed, Head Start has floundered since its inception. That there is real need is clear; however, a new way forward is essential. We propose a model, based on social pedagogy, that takes seriously and respectfully the lifeworld of the children and families involved, and works cooperatively to find a way forward for everyone instead of imposing an externally-driven system response to an inadequately understood lifeworld. In addition, this reconceptualization must move beyond the exclusiveness of compensatory programs to inclusiveness of all children and families. This approach offers hope both for a more just social world in general based on deliberative justice as well as attaining goals of student achievement and development.